AI-Powered Counterfeit Detection System - Magar, Anuja; Dere , K. D. (International Journal of Recent Advances in Engineering and Technology, 2025)
It leads to financial losses, endangering consumer safety and consequently placing a significant risk in the respective industry. With the auspicious growth of e- commerce, quality counterfeit detection solutions have become increasingly demanding. Artificial Intelligence (AI) essentially issued to detect fake product with a strongest of data of machine learning, deep learning and computer vision. Furthermore, the combination of AI and blockchain facilitates greater security and transparency in supply chains. This paper reviews many methods of detecting counterfeits using AI, as well as how these methods can be combined with blockchain to form a network.